Peptide‐Mimicking Poly(2‐oxazoline)s Displaying Potent Antimicrobial Properties. (30th October 2020) - Zhou, Min; Jiang, Weinan; Xie, Jiayang; Zhang, Wenjing; Ji, Zhemin; Zou, Jingcheng; Cong, Zihao; Xiao, Ximian; Gu, Jiawei; Liu, Runhui
Abstract: Poly(2‐oxazoline)s have excellent biocompatibility and have been used as FDA‐approved indirect food additives. The inert property of the hydrophilic poly(2‐oxazoline)s suggests them as promising substitutes for poly(ethylene glycol) (PEG) in various applications such as anti‐biofouling agents. It was recently reported that poly(2‐oxazoline)s themselves have antimicrobial properties as synthetic mimics of host defense peptides. These studies revealed the bioactive properties of poly(2‐oxazoline)s as a new class of functional peptide mimics, by mimicking host defense peptides to display potent and selective antimicrobial activities against methicillin‐resistant Staphylococcus aureus both in vitro and in vivo, without concerns about antimicrobial resistance. The high structural diversity, facile synthesis, and potent and tunable antimicrobial properties underscore the great potential of poly(2‐oxazoline)s as a class of novel antimicrobial agents in dealing with drug‐resistant microbial infections and antimicrobial resistance. Abstract : A POX on drug resistance ! Recently, poly(2‐oxazoline)s (POXs) were demonstrated to be a new class of functional peptide mimics to display potent antimicrobial activity against drug‐resistant bacteria in vitro and in vivo, with their antimicrobial mechanism tunable by varying the polymers' sidechain structures.